Knowing the Knowing. Non-dual Meditative Practice From an Enactive Perspective - Meling, Daniel (Frontiers in Psychology, 2022)
Within a variety of contemplative traditions, non-dual-oriented practices were developed to evoke an experiential shift into a mode of experiencing in which the cognitive structures of self-other and subject-object subside. These practices serve to de-reify the enactment of an observing witness which is usually experienced as separate from the objects of awareness. While several contemplative traditions, such as Zen, Mahāmudrā, Dzogchen, and Advaita Vedanta emphasize the importance of such a non-dual insight for the cultivation of genuine well-being, only very few attempts in contemplative science have turned toward the study of non-dual-oriented practices. This article starts from a recently developed theoretical cognitive science framework that models the requirements of a temporary experiential shift into a mode of experiencing free from cognitive subject-object structure. This model inspired by the enactive approach contributes theoretically grounded hypotheses for the much-needed rigorous study of non-dual practices and non-dual experiences. To do so, three steps are taken: first, common elements of non-dual-oriented practices are outlined. Second, the main ideas of enactive cognitive science are presented including a principled theoretical model of what is required for a shift to a pure non-dual experience, i.e. an experiential mode that is unbound by subject-object duality. Third, this synthesized theoretical model of the requirements for the recognition of the non-dual is then compared with a specific non-dual style of meditation practice, namely Mahāmudrā practice from Tibetan Buddhism. This third step represents a heuristic for evaluating the external coherence of the presented model. With this, the aim is to point towards a principled enactive view of non-dual meditative practice. In drawing the implications of the presented model, this article ends with an outlook toward next steps for further developing a research agenda that may fully address the concrete elements of non-dual practices.